Colombian inmigration in Spain: a state of art - Villarraga Orjuela, Hernán (Sociedad y Economía, 2010)
Colombian immigration in Spain: a state of the art Since the 1990s, immigration in Spain has acquired new statistical and sociodemographic dimensions. A shortage of workers in certain labor sectors has contributed to the attraction of immigrants from different parts of the world, including a large number of Colombians. A significant proportion of Colombians in Spain perform labor activities perceived undesirables by the Spanish population. In this paper, we present a review of the literature on Colombian immigration in Spain. We present a typology of the literature until the present and offer an extendedbibliography for those seeking further study on the topic.